Um estudo de técnicas da Inteligência Artificial aplicadas na distribuição de recursos em áreas geográficas - TELES, Ronneesley Moura (2011)
This paper studies a problem that is the distribution of resources in geographical areas. Many organizations, from taxis, to the military faces this problem in their daily operations. In essence, it tries to answer the question: What are the best places in which I place my assets in the geographic area X, according to a set of constraints Y? . To answer the question, we studied representation models of the problem, known techniques have been applied in Artificial Intelligence and Operations Research, such as: testing all combinations, greedy algorithms, heuristics and genetic algorithms. Algorithms were created and simulations were performed. Furthermore, Multiagent System was developed that implements one of algorithms developed. In evaluating the proposals made in this dissertation, it was considered the field of Electric Companies in the task of distributing vehicles in a city.